2020
DOI: 10.3390/pathogens9020076
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Clinical and Economic Impact of Switching from the 13-Valent Pneumococcal Conjugate Vaccine (PCV13) to the 10-Valent Pneumococcal Conjugate Vaccine (PCV10) in Italy

Abstract: Background: Invasive and non-invasive pneumococcal diseases are significant health and economic burdens, especially in children and the elderly. Italy included the 7-valent (PCV7) and 13-valent pneumococcal conjugate vaccine (PCV13) in the National Immunization Program in 2007 and 2010, respectively, allowing a dramatic reduction in the burden of pneumococcal disease. In the era of budget constraints, decision-makers may consider switching from the higher-valent, more costly PCV13, to the lower-cost PCV10. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…In 2017, the Italian Immunization Plan 2017–2019 recommended pneumococcal vaccinations for individuals aged ≥65 years with a single dose of PCV13 followed by PPV23 [ 15 ]. Despite these recommendations, the vaccination uptake remains low in both at-risk and older adults [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…In 2017, the Italian Immunization Plan 2017–2019 recommended pneumococcal vaccinations for individuals aged ≥65 years with a single dose of PCV13 followed by PPV23 [ 15 ]. Despite these recommendations, the vaccination uptake remains low in both at-risk and older adults [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The model structure has been described in detail elsewhere. 26 , 27 , 30 Briefly, the model uses retrospective country-level observed surveillance data on serotype-specific pneumococcal disease to estimate prospective serotype disease behavior. Therefore, for vaccine serotypes contained in both PCV10 and PCV13, as well as non-vaccine serotypes, the model predicts future disease behavior from retrospective real-world data in the population dependent on which vaccine is being evaluated.…”
Section: Methodsmentioning
confidence: 99%
“…Age-specific all-cause mortality rates per 100,000 for each age group were taken from IBGE 2018 data. 30 Age-specific case-fatality rates (CFR) for bacteremia, meningitis, and hospitalized pneumonia were taken from the most recent year of Novaes et al 33 which calculated CFR from the number of deaths/confirmed cases for each clinical syndrome registered in the SIH-SUS. The analysis used CFR from SIH-SUS for hospitalized pneumonia and meningitis ( Table 1 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cost-effectiveness model used for this Brazil study uses the same assumptions as many other peer-reviewed studies, including country examples for Mexico, Colombia, Finland, Netherlands, Canada, Malaysia, Italy, and Australia. 5–10 This scientific methodology used for pneumococcal disease serotype trends has been recognized and is a strength of this study because we were able to show with numerous predictions from multiple countries the possible range of outcomes when switching to PCV13. These trendlines serve as a proxy for what Brazil can expect for a PCV13 NIP infant program and ultimately capture variations in uptake, antimicrobial resistance, underlying serotype dynamics, indirect effect, and historical schedules observed in other countries.…”
Section: Structural Uncertainty Was Tested and Confirmed Conclusion T...mentioning
confidence: 97%